INVESTIGATING THE STUDENTS’ PERCEPTIONS TOWARD THEIR MOBILE LEARNING EXPERIENCES AT THE FIFTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT: A Descriptive Study - Meydina, Erika; Dalle, M. Basri; Ma'ruf, Amar (FKIP Unismuh Makassar, 2018)
This research aimed to find out the sorts of mobile learning experiences used by the fifth semester students and their perceptions toward mobile learning in learning English. This research was conducted through descriptive quantitative method. The population was the fifth semester students of Muhammadiyah University of Makassar and took 60 students as the sample. The researcher used instrument to find out the sorts of students’ mobile learning experiences and their perceptions.Findings in this research are almost all students’ mobile learning experiences are from smartphone. It showed 100% students chose smartphone, 18% chose laptop, 17% chose netbook, and 5% chose MP3 Player. Then, the result of students’ perceptions showed students are (85%) strongly agree that M-Learning is engaging, (82%) strongly agree M-Learning is convenient, (79%) agree M-Learning is flexible and (79%) agree M-Learning is interactive. Based on the research findings above, it could be concluded that students’ has experienced smartphone as their Mobile learning, and mobile learning is effective as a learning tool to learn English.